2017
DOI: 10.1177/0020731416689552
|View full text |Cite
|
Sign up to set email alerts
|

Still Elegantly Muddling Through? NICE and Uncertainty in Decision Making About the Rationing of Expensive Medicines in England

Abstract: Calnan, Michael .W. and Hashem, Ferhana and Brown, P (2017) Health and Care Excellence) as it regulates the provision of expensive new drugs within the English NHS on cost-effectiveness grounds. Ostensibly this is a highly rational process by which the regulatory mechanisms absorb uncertainty but in practice decision-making remains highly complex and uncertain. This paper draws on ethnographic data interviews with a range of stakeholders and decision-makers (n=41), observations of public and closed appraisal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 41 publications
0
40
0
1
Order By: Relevance
“…This research identifies the implicit social influences about how decisions are made and suggest that the decision-making process is characterised by a form of navigation, (rather than ‘muddling through’) where the decision-makers navigate their way through the uncertainties inherent in what is formally described as evidence-based decision-making process. 8 The paper suggests that ‘cost effectiveness analysis which has been applied with some success to allocative decision-making at a macro level’ (p. 11). 2 The evidence from ethnographic studies 9 suggest that this account may only present a partial picture of the nature of the decision-making process and what shapes it.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This research identifies the implicit social influences about how decisions are made and suggest that the decision-making process is characterised by a form of navigation, (rather than ‘muddling through’) where the decision-makers navigate their way through the uncertainties inherent in what is formally described as evidence-based decision-making process. 8 The paper suggests that ‘cost effectiveness analysis which has been applied with some success to allocative decision-making at a macro level’ (p. 11). 2 The evidence from ethnographic studies 9 suggest that this account may only present a partial picture of the nature of the decision-making process and what shapes it.…”
mentioning
confidence: 99%
“…There was also uncertainty and ambiguity associated with the level of technicality and complexity of the information provided. 8 Agencies such as NICE recognise, attempt to address and try to resolve some of these epistemological uncertainties particularly through quantitative techniques. 12 However, the evidence 8 also suggested that navigation of these layers of uncertainty was (partially) managed through practical rationality and various forms of trust at different levels.…”
mentioning
confidence: 99%
“…Evidence from this study did show that the overriding priority of the committee was to appraise the technology in terms of cost‐effectiveness and the extent to which it fell in or outside the threshold set by NICE . In one of our cases, the technology was far too expensive and a decision not to recommend was made after two meetings which may explain why there was limited patient expert involvement.…”
Section: Discussionmentioning
confidence: 78%
“…The study used a prospective design to follow three pharmaceutical products through the STA process, which were chosen for variation in the socio‐cultural resonance of the illness they were designed to treat. The final selection included: a drug treating a less “prominent” but prevalent chronic illness (Case Study X); a drug treating a high profile condition (Case Study Y); and lastly, a drug which treated a rare but life‐threatening condition (Case Study Z) …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, better practices could be achieved by implementing the 10 QDMPs into agency processes that promote having a structured approach to decision making (QDMP 1), assigning values to decision criteria (QDMP 3), evaluating different alternatives (QDMP 5), and new information (QDMP 7), and more importantly, evaluating different influences and biases (QDMP 4) to ensure that structured decisions are made during the review of medicines. It would be of interest to widen the scope of such studies to other regulatory agencies, as well as HTA committees in order to address the uncertainty surrounding the process for appraising whether or not medicines should be recommended for reimbursement (Calnan et al, 2017). …”
Section: Discussionmentioning
confidence: 99%